Beispiel Nr: 47
$ \text{Gegeben:} y=ax^2+bx+c \\ \text{Gesucht:} \\ \text{Scheitel und Scheitelform}\\ \text{Definitions- und Wertebereich} \\ \text{Nullstellen - Schnittpunkt mit der x-Achse} \\ \text{Faktorisiere Form} \\ \text{Scheitel} \\ Eigenschaften\\ \textbf{Gegeben:} \\ y=-\frac{1}{3}x^2+2x+5\\ \\ \textbf{Rechnung:} \\\bullet \text{Funktion} \\ y=-\frac{1}{3}x^2+2x+5\\ \\ \bullet \text{Scheitelberechnung } \\ \begin{array}{l|l|l} \begin{array}{l} \text{quadratische Ergänzung } \\ \hline y=-\frac{1}{3}x^2+2x+5 \\ y=-\frac{1}{3}(x^2-6x-15) \\ y=-\frac{1}{3}(x^2-6x+3^2-3^2-15) \\ y=-\frac{1}{3}[(x-3)^2-3^2-15] \\ y=-\frac{1}{3}[(x-3)^2-9-15] \\ y=-\frac{1}{3}[(x-3)^2-24] \\ y=-\frac{1}{3}(x-3)^2+8 \\ Scheitel(3/8) \end{array} & \begin{array}{l} \text{quadratische Ergänzung } \\ \hline y=-\frac{1}{3}x^2+2x+5 \\ y=-\frac{1}{3}(x^2-6x)+5 \\ y=-\frac{1}{3}(x^2-6x+3^2-3^2)+5 \\ y=-\frac{1}{3}[(x-3)^2-3^2]+5 \\ y=-\frac{1}{3}[(x-3)^2-9]+5 \\ y=-\frac{1}{3}(x-3)^2+3+5 \\ y=-\frac{1}{3}(x-3)^2+8 \\ Scheitel(3/8) \end{array} & \begin{array}{l} \text{Scheitelformel} \\ \hline y=-\frac{1}{3}x^2+2x+5 \\ xs=-\frac{2}{2\cdot \left(-\frac{1}{3}\right)} \\ xs=3 \\ ys=5-\frac{2^2}{4\cdot\left(-\frac{1}{3}\right)} \\ ys=8 \\ Scheitel(3/8)\\ y=-\frac{1}{3}(x-3)^2+8 \end{array} \\ \end{array} \\ \\ \\\bullet\text{Definitions- und Wertebereich:}\qquad \mathbb{D} = \mathbb{R} \qquad \mathbb{W} = ]-\infty;8]\\ \\=-\frac{1}{3}(x+1,9)(x-7,9)\\ \\\bullet \text{Nullstellen / Schnittpunkt mit der x-Achse:} \\y=-\frac{1}{3}x^2+2x+5 = 0 \\ \begin{array}{l|l|l} \begin{array}{l} \text{a-b-c Formel}\\ \hline \\ -\frac{1}{3}x^{2}+2x+5 =0 \\ x_{1/2}=\displaystyle\frac{-2 \pm\sqrt{2^{2}-4\cdot \left(-\frac{1}{3}\right) \cdot 5}}{2\cdot\left(-\frac{1}{3}\right)} \\ x_{1/2}=\displaystyle \frac{-2 \pm\sqrt{10\frac{2}{3}}}{-\frac{2}{3}} \\ x_{1/2}=\displaystyle \frac{-2 \pm3,27}{-\frac{2}{3}} \\ x_{1}=\displaystyle \frac{-2 +3,27}{-\frac{2}{3}} \qquad x_{2}=\displaystyle \frac{-2 -3,27}{-\frac{2}{3}} \\ x_{1}=-1,9 \qquad x_{2}=7,9 \end{array}& \begin{array}{l} \text{p-q Formel}\\ \hline \\ -\frac{1}{3}x^{2}+2x+5 =0 \qquad /:-\frac{1}{3} \\ x^{2}-6x-15 =0 \\ x_{1/2}=\displaystyle -\frac{-6}{2}\pm\sqrt{\left(\frac{\left(-6\right)}{2}\right)^2- \left(-15\right)} \\ x_{1/2}=\displaystyle 3\pm\sqrt{24} \\ x_{1/2}=\displaystyle 3\pm4,9 \\ x_{1}=7,9 \qquad x_{2}=-1,9 \end{array}\\ \end{array}\\ \underline{x_1=-1,9; \quad1\text{-fache Nullstelle}} \\\underline{x_2=7,9; \quad1\text{-fache Nullstelle}} \\ \\ \bullet \text{Vorzeichentabelle:} \\ \begin{array}{|c|c|c|c|c|c|c||} \hline & x < &-1,9&< x <&7,9&< x\\ \hline f(x)&-&0&+&0&-\\ \hline \end{array}\\ \\ \underline{\quad x \in ]-1,9;7,9[\quad f(x)>0 \quad \text{oberhalb der x-Achse}}\\ \\ \underline{\quad x \in ]-\infty;-1,9[\quad \cup \quad]7,9;\infty[\quad f(x)<0 \quad \text{unterhalb der x-Achse}}$